Gq rather than G11 preferentially mediates nociceptor sensitization - Wirotanseng, Laura Nikita; Kuner, Rohini; Tappe-Theodor, Anke (Molecular pain, 2013)
Background: The Gq/11-protein signaling mechanism is essential throughout the nervous system, but little is known about the contribution of the individual G-protein GPCR signaling branches towards nociceptor activation and their specific role on nociceptor sensitization. We aimed to unravel the contribution of the Gq/11-signaling pathway towards nociceptor activation via a variety of classical inflammatory mediators signalling via different G-protein GPCRs and investigated the specific contribution of the individual Gq and G11, G-Proteins in nociceptors. Findings: Using different transgenic mouse lines, lacking Gαq, Gα11, or both α-subunit of the G-proteins in primary nociceptive neurons, we analyzed the mechanical- and heat-sensitivity upon application of different GPCR-agonists that are known to play an important role under inflammatory conditions (e.g. ATP, Glutamate, Serotonin etc.). We found that the Gq/11-GPCR signaling branch constitutes a primary role in the manifestation of mechanical allodynia and a minor role in the development of thermal hyperalgesia. Moreover, with respect to the mediators used here, the Gq-protein is the principle G-protein among the Gq/11-protein family in nociceptive neurons leading to nociceptor sensitization. Conclusions: Our results demonstrate that the Gq/11 signaling branch plays a primary role in nociceptor sensitization upon stimulation with classical GPCR ligands, contributing primarily towards the development of mechanically allodynia. Moreover, the deletion of the individual G-proteins led to the finding that the Gq-protein dominates the signalling machinery of the Gq/11 family of G-proteins in nociceptive neurons.